Divide We Stand - Miller, Jason A. (My University, 2003)
During the height of the Cold War, a new form of conflict among Canadian workers emerged along political lines. In some cases, the major source of conflict shifted from that of union versus management to left-wing union versus right-wing union. This thesis focusses on such an inter-union battle between the International Union of Mine, Mill and Smelter Workers and the United Steelworkers of America in Sudbury. Ontario from 1942 to 1969. ln this analysis, which attempts to incorporate the perspectives of the unions, the mine operators, and the Catholic Church and its affiliate organizations, it will be shown that despite the profound influence of the union executives, the media, the Church, and other prominent figures, the final decision regarding which union to joinwas ultimately made by the rankand- file members at Inco and Falconbridge (with the miners at Inco choosing the Steelworkers as their bargaining agent while the miners at Falconbridge chose to remain with Mine-Mill).
[missing pages 130 and 138]
Keywords: History; History